Shale gas content evaluation for deep strata and its variation: a case study of Weirong, Yongchuan gas fields in Sichuan Basin - Haikun SU; Haikuan NIE; Shaobin GUO; Zhenheng YANG; Donghui LI; Chuanxiang SUN; Ting LU; Mi LIU (Shiyou shiyan dizhi, 2022)
The exploration and development of shale gas in China are recently focusing on the deep layers. However, the occurring characteristics of shale gas under high temperature and high pressure are not clear, which imposes great restrictions to deep shale gas development on a massive scale. Taking the deep shale in Weirong and Yongchuan regions of Sichuan Basin as research objects, for core samples with different organic carbon content and porosity, the isothermal adsorption experiments and porosity testing at high temperature and high pressure (135 ℃, 80 MPa) were carried out, and the theoretical values of shale adsorption gas, free gas and total gas content and compared with actual values. Results show that: (1) The content of adsorbed gas in deep shale increases gradually with pressure growing up. When the pressure surpasses 40 MPa, the increment flattens out, making 4.46 cm3/g the maximum of adsorbed gas content. (2) The theoretical gas content of shale increases with the growing formation pressure. The total gas content reaches its maximum 11.3 cm3/g under 80 MPa, which is made up with calculated free gas with an average of 6.8 cm3/g and adsorbed gas with an average of 4.5 cm3/g, accounting for about 60% and 40% of the total gas content, [JP]respectively. The ratio of free gas versus adsorbed gas gets larger with a greater buried depth. (3) Based on field desorption experiment, the actual measurement maximum gas content of well Weiye 11-1 is 5.95cm3/g, the minimum value is 3.29cm3/g, and the average content is 4.52 cm3/g. Compared with the theoretical value of 10.3 cm3/g, the result indicates that nearly 50% of gas leaked in the process of formation uplift, displaying the complexity of the deep shale gas preservation conditions. It is recommended to strengthen research on preservation conditions.